1992
DOI: 10.1021/ma00049a038
|View full text |Cite
|
Sign up to set email alerts
|

Proton NMR chemical shift induced by ionic association on a poly(ethylene oxide) chain

Abstract: When a polymer strongly binds metal ions in solution, a substantial number of counterions can also be bound to it, if the polarity of the solvent is not too high. This is actually obeerved for poly(ethy1ene oxide) (PEO) and sodium thiocyanate in nitromethanel and PEO and barium salts in methanol.2 The phenomenon may be regarded as an ionic association between the cation of the PEO-metal complex and counteranion and resembles the ion condeneation of polyelectrolytes. Although our previous conductivity studies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…22,23 It has also been reported that Ba 2+ binds more strongly than Sr 2+ among divalent cations. 19,20 Yet, experimental techniques and conditions and, particularly, the sometimes complex models used have varied between studies, and therefore it remains difficult to make quantitative comparisons. This calls for systematic and preferably quantitative studies including, ideally, all relevant ions previously investigated; one then hopes to observe trends that may have remained hidden.…”
Section: ■ Introductionmentioning
confidence: 99%
“…22,23 It has also been reported that Ba 2+ binds more strongly than Sr 2+ among divalent cations. 19,20 Yet, experimental techniques and conditions and, particularly, the sometimes complex models used have varied between studies, and therefore it remains difficult to make quantitative comparisons. This calls for systematic and preferably quantitative studies including, ideally, all relevant ions previously investigated; one then hopes to observe trends that may have remained hidden.…”
Section: ■ Introductionmentioning
confidence: 99%
“…(c) Reduction of bound Ag + ions with cavities (pseudocrown ether structure) [53][54][55][56][57][58][59][60][61] through oxidation of the oxyethylene and oxypropylene segments by the metal center [51].…”
Section: Proposed Mechanism On Silver Ion Reduction By Peo-ppo Block mentioning
confidence: 99%
“…This suggests an increment of nuclear shielding effect around the tertiary amine of LDC, which was caused by acidic IDM molecules acting as hydrogen donors. 1 H-NMR spectroscopy has frequently been applied to the investigation of ionic association, such as ion pair formation between polyethylene oxide and barium salts 21 and in the imidazolium halide salts as ionic liquid 22 . Downfield shift of 1 H signal was induced by the shift of the ion pair equilibrium toward tight ion pairs from free ions.…”
Section: Miccs-1 H-nmrmentioning
confidence: 99%